SEBUAH STUDI MENGENAI IMPLEMENTASI PERJANJIAN KERJA YANG MENYIMPANG DARI PERUNDANG-UNDANGAN DIKAITKAN DENGAN MORALITAS - Tundjung Herning Sitabuana; Mikael Brian (Faculty of Law - Tarumanagara University, 2021)
The use of fixed-time employment agreements is commonplace in Indonesia. However, some companies use term employment agreements to make a profit. Many companies do not realize that taking profits by monopolizing workers on fixed-time employment agreements is a violation of the rights of workers who work in the company. The extension of the fixed-time work agreement must be in accordance with the applicable laws and regulations, particularly Law Number 13 of 2003 concerning Manpower. However, as mentioned by the author, many companies applying for work contract extensions still deviate from the law. The author uses the juridical normative research method, namely in the activities of describing legal norms, formulating legal norms, and implementing legal norms, they provide research on understanding the normative problems faced by normative law. Therefore, in this article, the author will analyze the implementations of the work agreement that deviates from the legal provisions and conduct a more in-depth study, if this happens, the company and workers will get the legal consequences. In this journal, the author tries to elaborate the relationship between the invalid fixed-term employee agreement and morality.